Development of application-based learning for autistic students - Sigit, Cahyo Nugroho; Muarifin, Muarifin; Darmawan, Arief; Amin, Lutfil (Journal of Science and Education (JSE), 2024)
Poor levels of physical activity, cognitive ability, and social interaction are demonstrated in autistic children. These learning barriers in the school environment must be explicitly managed, including in terms of designing objectives, materials, methods, tools, and evaluations to achieve the actual learning objectives. Due to the complex learning barriers in autistic children, conventional learning must be collaborated with assistive technology. Based on these problems, this research aims to develop a drag-and-drop game application equipped with basic motion animation instructions. The research and development method uses the ADDIE model, which consists of five stages. The effectiveness test is carried out with a one-group pretest-posttest design, with treatment for three days and a duration of 105 minutes. With the results of the research based on the results of this overall trial, a score of 81.1% was obtained, which, when viewed from the classification table of product effectiveness scores, was included in the category of very valid for use in learning. The effectiveness test obtained a Sig value. (2-tailed) 0.000 <0.05 means Hₐ is accepted and has a significant effect on student learning outcomes. This development concludes that although the development results can be used well, teachers' ability to manage classrooms remains dominant in maintaining and regulating the learning focus of children with autism. Therefore, further research can develop and collaborate between assistive technology and learning models for physical education that can be applied and adapted to both group and individual physical activities for autistic children.